Legal Protection For Book Piracy Traded Through Marketplaces In Indonesia - Amalia, Annisa Dinda; Badriyah, Siti Malikhatun (Batulis Civil Law Review, 2024)
Introduction: According to Law Number 28 of 2014 concerning Copyright, an act is considered a Copyright violation if it violates the exclusive rights of the creator, which includes the right to publish or reproduce his work and the right to give permission or prohibit other people from doing so. create, reproduce or broadcast it without their consent.Purposes of the Research: This research aims to analyze how the law accommodates the protection of book piracy cases in the marketplace which is easy to do.Methods of the Research: The research method used in this paper is a normative legal research method. A conceptual approach and a law-based approach were used in this research. Legal materials are identified through document study. The approach and analysis applied is qualitative.Results of the Research: The research method used in this paper is a normative legal research method. A conceptual approach and a law-based approach were used in this research. Legal materials are identified through document study. The approach and analysis applied is qualitative.